Bilateral Knee Osteonecrosis After Intraarticular Concomitant Local Anesthetic and Corticosteroid Injection: A Case Report (Annals of Medical Research, 2021)
None
Keywords: Intraarticular İnjections; Corticosteroid; Knee Osteoarthritis.